Envejecimiento y corresidencia multigeneracional en Chile entre 1982 y 2017 - Herrera Ponce, María Soledad; Fernández Lorca, María Beatriz (El Colegio de México A.C., 2025)
The article describes the evolution of the multigenerational co-residence in Chile, with emphasis on the variables associated with it among people aged 60 or over, using the complete databases of the National Population Censuses of 1982, 1992, 2002, 2012 and 2017. Multigenerational co-residence is defined as an older people living with a son or daughter aged 25 or older and/or with a grandchild with or without the intermediate generation. While three-generation arrangements were halved in the period studied, the number of older people co-residing only with adult children aged 25 or over (without grandchildren) increased, so the decline in the proportion of Chilean older people living in multigenerational arrangements has not been so abrupt. It can be concluded that multigenerational co-residence occurs mainly due to adult children who stay longer in their parents’ homes and for elderly widows who go to live to a child’s home.